Extended Stability of Restriction Enzymes at Ambient Temperatures. (September 2000) - Clark, Jason; Harrison, Jennifer C.; Mdegela, Robinson H.; March, John B.
The stability of restriction enzymes as supplied by manufacturers without any modification has been examined. No reduction in activity was observed for three enzymes ( Hin dIII, Eco RI and Tsp 509I) held at ambient temperature or 4°C for the period of study (12 months), while activity was observed for up to 12 weeks after storage at 37°C, which was considerably better than following desiccation with trehalose, a recognized preservation technique. A larger trial of 23 different restriction enzymes held at room temperature for one week showed that all enzymes retained significant activity. As a practical demonstration of the usefulness of this finding, enzymes were posted to Africa by conventional mail (cost 1 US) and shown to retain activity upon arrival after three weeks in transit (compared to a cost of 1000 US by cold-chain transportation). Supplying enzymes to third-world markets should now be possible by removing the necessity for cold-chain transport. After arrival, enzymes can simply be stored in a standard domestic refrigerator.